Transregional Cooperation of Austrian Federal Lands with Eastern Regions and Countries in 20th-21st Centuries - E. O. Muslimova; A. G. Nesterov; V. A. Katuntsev (Научный диалог, 2025)
This article examines the formation and development of transregional relationships between the federal lands of Austria and Eastern countries and regions. It highlights the interaction between the lands and the federal government in shaping regional foreign policy strategies. The study presents an analysis of the regulatory framework governing the international and foreign policy activities of Austria’s regions, based on a review of national legislation. The paper addresses the traditional close ties of Austrian regions with partners from neighboring states. Additionally, it explores partnerships with distant Eastern territories, including Chinese provinces, Japanese prefectures, Iran, Turkey, Israel, and Middle Eastern countries. The research is grounded in an original comprehensive methodology that incorporates principles of dynamism, systemic thinking, and holistic analysis, as well as historical-systemic and historical-comparative approaches, alongside theoretical foundations from multilevel governance and federalism theories. It is established that China serves as a priority partner for many Austrian lands, with various Chinese provinces engaging based on the resource and infrastructure capabilities of Austria’s regions.